Lipid enhancement in oleaginous nannochloropsis sp. under nitrate limitation for future bioenergy production - Palanisamy, Karthick Murugan; Bhuyar, Prakash; Mohd Hasbi, Ab. Rahim; Vadiveloo, Ashiwin; Al-Dhabi, Naif Abdullah; Govindan, Natanamurugaraj; Maniam, Gaanty Pragas (Wiley and Hindawi, 2023)
Microalgae possess high oil content, exhibit rapid growth rates and biomass productivity, and leave a minimal environmental footprint, making them highly attractive for biofuel applications. Consequently, this present study is aimed at evaluating the impact of nitrogen starvation on the marine microalgae Nannochloropsis sp. to enhance lipid accumulation. The microalga culture was grown under an irradiance of 120 μmol photon m-2 s-1, temperature °C, continuous air-CO2, and with different concentrations of sodium nitrites over a 14-day cultivation period. From the results, it was found that the growth of the strain decreased under limited nitrogen conditions. After harvesting, the cells in the supernatant were regenerated by cultivating in double concentration of media. The results showed that on the 12th day, the highest lipid content was achieved, reaching  wt.% of the dry weight under nitrogen limitation. The composition of the obtained lipid consisted of 18.0 wt.% saturated fatty acids, 72.38 wt.% monounsaturated fatty acids, and 8.95 wt.% polyunsaturated fatty acids. The lipid composition was dominated by monounsaturated oleic acid ( wt.%), saturated palmitic acid ( wt.%), and polyunsaturated linoleic acid ( wt.%). The findings of this study demonstrated that limiting nitrogen availability enhanced lipid accumulation in Nannochloropsis sp. Despite experiencing inhibited growth, this microalga species shows great potential for the large-scale cultivation of lipids and essential fatty acids. These results contribute to understanding the relationship between nitrogen availability and lipid metabolism in microalgae, providing valuable insights for optimizing lipid production in the context of biofuel and biotechnology applications.